علاقة اهم مظاهر الانتباه بأداء حكام الريشة الطائرة اثناء قيادة المباريات - أحمد, مازن عبد الهادي; ابراهيم, طاهر يحيى (Sulaimani Journal for Humanities, 2018)
Accompanied Sport badminton process of development and progress and entered into their training process of the latest findings of the world of high possibilities that the rest of the sports and longer rulers quill main column of the game where they make up the main task of the elements to take out the game as required and managed the game by (13) sentenced them to power to implement all the articles of the law in cooperation with the general supervisor of the match. And that mental processes such as attention is one of the important issues related to the decision- making and in the badminton importance of attention emerged clearly for the rulers in terms of performance accuracy and this proves the importance of attention in the game in order to give a clear role in the referees' decisions and to achieve the tasks that must be based their rulers. The attention is one of the most essential elements in the success of the government and its ability to control the course of events of the game because they lead to the result that the referees make decisions clearly as the decision affects the outcome of the game and the game up to the basic interest rate which is the excitement and fun. And show the importance of research through knowledge of the role of the manifestations of attention in making the right decisions for referees in badminton process. The researchers believe that there is a lack of interest in the study of the subject of attention for the referees as well as merely technical and physical tests and not to subject judges to the psychological tests and assessments affecting the performance level of the game in general, which is in itself a problem in the development level of the game. Find a problem in reaching a knowledge of the relationship between the most important aspects of attention and accuracy performance badminton referees and develop appropriate solutions, which it considers necessary and important to improve the performance of the referees badminton accuracy were determined. The research aims to identify the performance of badminton rulers level, in addition to the most important aspects of attention and the relationship between the level of performance and manifestations of attention and the difference between the rulers of the arena and the transmitter in the level of performance and manifestations of attention. The researchers used the descriptive approach to address the problem of their research, have reached research sample (20 judgments) of the rulers of the first class in the Middle Euphrates region of origin (28 judgment), and thus the sample proportion will reach 71.42%, the researchers used a test (Borden - Atvemun) and this is one test athletes for tests, used to measure the five aspects of attention, namely, (sharpness and consistency, focus and distribution and transmission). The researchers concluded the following: 1- Rulers arena group achieved a high correlation between the level of performance and to focus attention and intensity of attention relationship. 2. There was a significant correlation between the level of performance and to focus attention to the transmission rulers in badminton relationship. 3. There is a significant correlation between the level of performance and intensity of attention to the transmission rulers in badminton relationship. The researchers recommend, to: - 1. The need to hold special training to develop the focus of attention and intensity of attention to the badminton rulers. 2. The need to carry out tests for levels of performance on a regular basis for all badminton rulers, according to their positions (referee, was sentenced send, monitor line)
Keywords: performance; badminton rulers; the manifestations of attention